Pandemic fears, family interference with work, and organizational citizenship behavior: Buffering role of work-related goal congruence - De Clercq, D.; Pereira, R. (European Management Review, 2022)
Pandemic fears are nearly inescapable, with likely effects on organizational citizenship behavior. This article considers the potential mediating influence that arises if employees experience family interference in their work, as well as the potential buffering role of work-related goal congruence, in this relationship. Survey data were collected from employees who work in the information technology (IT) consulting sector in Portugal. The research hypotheses were tested with a bootstrapping approach, based on the Process macro, which enables the simultaneous assessment of mediation and moderation effects. The empirical results show that employees' ruminations about the coronavirus diminish their voluntary work behaviors, because their family-related stress interferes with their work. Such harmful outcomes are less prominent among employees who perceive work-related problems as mutually shared. This study accordingly reveals how organizations can limit the detrimental effects of the COVID-19 pandemic by aligning the work-related goals of their employee bases.